2015
DOI: 10.1109/tbme.2015.2388611
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Peritoneal Microbubble Oxygenation Therapy in a Rabbit Model of Hypoxemia

Abstract: Abstract-Alternative extrapulmonary oxygenation technologies are needed to treat patients suffering from severe hypoxemia refractory to mechanical ventilation. We previously demonstrated that peritoneal microbubble oxygenation (PMO), in which phospholipid-coated oxygen microbubbles (OMBs) are delivered into the peritoneal cavity, can successfully oxygenate rats suffering from a right pneumothorax. This study addressed the need to scale up the procedure to a larger animal with a splanchnic cardiac output simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…255,256,257,258 Moreover, the opportunity exists currently to further test the effects of supplemental O 2 ; more modern standards of clinical trials such as establishing dose/response, effects of treatment duration, minimum dosing necessary etc. should surely be attempted as a simple yet potentially effective intervention.…”
Section: Potential Drug Targets Of Important Placental Pathways Imentioning
confidence: 99%
“…255,256,257,258 Moreover, the opportunity exists currently to further test the effects of supplemental O 2 ; more modern standards of clinical trials such as establishing dose/response, effects of treatment duration, minimum dosing necessary etc. should surely be attempted as a simple yet potentially effective intervention.…”
Section: Potential Drug Targets Of Important Placental Pathways Imentioning
confidence: 99%
“…Therefore, we aimed to identify other methods to supply oxygen promptly, particularly when encountered with above situations, in order to facilitate resuscitation, thereby providing additional time for tracheotomy. Previous studies have demonstrated that oxygen supply via peritoneum is feasible by direct abdominal ventilation or intraperitoneal infusion with oxygen carriers [5,8,12,13,[15][16][17][18][19] .However, these methods are complex and cannot be performed immediately; therefore, they are not suitable for emergency resuscitation in the operating room.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be used for extra-pulmonary oxygenation [11] . Previously, peritoneal oxygenation has been shown to moderately increase systemic arterial partial pressure of oxygen in rabbit, rat, and pig models [5,[12][13][14] via direct abdominal ventilation or intra-peritoneal infusion with oxygen carriers, such as perfluorocarbon, red blood cells, or oxygen micro-bubbles [5,8,12,13,[15][16][17][18][19] .Hence, peritoneal oxygenation has long been desired for extra-pulmonary oxygenation, as it is easy to perform, compared to use of an extracorporeal circuit.…”
mentioning
confidence: 99%
“…Various characterization techniques have been applied to characterize MNBs. Optical and fluorescence microscopy can reveal micron-sized bubbles, while dynamic light scattering (DLS) and other optical particle counters can be used to determine the size of the nanobubbles [8,10,13,50,72]. SEM and TEM techniques have been used to visualize MNBs [12].…”
Section: Characterization Techniques For Mnbsmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is another treatment mechanism that is oxygen-dependent for the generation of reactive oxygen species (ROS), and the increased oxygen level enhances the effectiveness of PDT [6,7]. Hypoxemia or low blood oxygen level occurs in patients suffering from severe lung injury, airway obstruction, reduced cardiac output, or any critical illness, and hypoxemia is responsible for an increased mortality rate [2,8,9]. Hypoxemia may cause cardiac arrest or organ damage and neurological complexities owing to low oxygen supply to the brain [2,10].…”
Section: Introductionmentioning
confidence: 99%